Adaptive and maladaptive behavior during the COVID-19 pandemic: The roles of Dark Triad traits, collective narcissism, and health beliefs - Nowak, Bartłomiej; Brzóska, Paweł; Piotrowski, Jarosław; Sedikides, Constantine; Żemojtel-Piotrowska, Magdalena; Jonason, Peter K. (Personality and individual differences, 2020)
In a nationally representative sample from Poland (N = 755), we examined the relationships between the Dark Triad traits (i.e., psychopathy, Machiavellianism, and narcissism) and collective narcissism (i.e., agentic and communal) on the one hand, and behaviors related to the COVID-19 pandemic at (1) the zero-order level, at (2) the latent variance level, and (3) indirectly through health beliefs about the virus (i.e., the health belief model) on the other. We focused on preventive and hoarding behaviors as common reactions toward the pandemic. Participants characterized by the Dark Triad traits engaged less in prevention and more in hoarding, whereas those characterized by collective narcissism engaged in more hoarding only. Coronavirus-related health beliefs mediated patterns of prevention (fully) and hoarding (partially) in the latent Dark Triad (Dark Core) and collective narcissism. However, specific beliefs worked in opposite directions, resulting in a weak indirect effect for prevention and a null indirect effect for hoarding. The results point to the utility of health beliefs in predicting behaviors during the pandemic, explaining (at least in part) problematic behaviors associated with the dark personalities (i.e., Dark Triad, collective narcissism). •Examined dark personality correlates and health beliefs related to the COVID-19•Correlated the Dark Triad traits with less prevention and more hoarding•Collective narcissism was only associated with more hoarding.•Health beliefs mediated patterns of prevention and hoarding.